(untitled) (Journal of Current and Advance Medical Research, 2018)
Background: There are several diseases related with the patients suffering from focal soft tissue rheumatism. Objective: The purpose of the present study was to observe the associated diseases among the patients suffering from focal soft tissue rheumatism. Methodology: This descriptive type of cross-sectional study was carried out in the Department of Physical Medicine and Rehabilitation at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from March 2006 to August 2006 for a period of 6(six) months. The patients presented with focal soft tissue rheumatism were selected from the Department of Physical Medicine and Rehabilitation who were referred from other outpatient department of Bangabandhu Sheikh Mujib Medical University, Dhaka and also from general practitioners outside the hospital. The different associated diseases were recorded during the data collection. Result: A total of 44 patients were recruited who were presented with different focal soft tissue rheumatism. The incidence of different soft tissue rheumatism cases were Tennis elbow 20(85.0%), De-Quervain`s disease 12(51.0%), Trigger fingers 8(34.0%) and Golfers elbow 4(17.0%). Diabetes mellitus was found in 8(18.0%) cases. Hypertension was detected in 10(23.0%) cases. Patients presented with hypertension and diabetes mellitus were found in 6(14.0%) cases. Peptic ulcer disease was found in 12(27.0%) cases. However, others diseases were found in 8(18.0%) cases. Conclusion: In conclusion diabetes mellitus, hypertension and peptic ulcer disease are the most common diseases found among the focal soft tissue rheumatism patients. Journal of Current and Advance Medical Research 2018;5(1):19-22